Salutogenic Effects of Greenspace Exposure: An Integrated Biopsychological Perspective on Stress Regulation, Mental and Physical Health in the Urban Population - Varadarajan Suchithra; Herchet Marilisa; Mack Matthias; Hofmann Mathias; Bisle Ellen; Sayer Emma; Kolassa Iris-Tatjana (Open Psychology)
Globally, urbanization is associated with increased risk for physical and mental diseases. Among other factors, urban stressors (e.g. air pollution) are linked to these increased health risks (e.g. chronic respiratory diseases, depression). Emerging evidence indicates substantial health benefits of exposure to greenspaces in urban populations. However, there is a need for an overarching framework summarizing the plausible underlying biological factors linked to this effect, especially within the context of stress regulation. Therefore, by outlining the effects of greenspace exposure on stress parameters such as allostatic load, oxidative stress, mitochondria, and the microbiome, we conceptualize an integrated biopsychological framework to advance research into the salutogenic and stress-regulatory potential of greenspace exposure. In addition, we discuss the understudied potential health benefits of biogenic volatile organic compounds. Our perspective highlights the potential for innovative greenspace-based interventions to target stress reduction, and their prospect as add-ons to current psychotherapies to promote mental and physical health in urban populations.